Investigating the blockchain technologies influences on the performance of road freight transportation management systems using network analysis technique - Ahmad Negravi; Omid Titidezh (تصمیم گیری و تحقیق در عملیات)
Purpose: This study seeks to assess the significant effects of blockchain, as a new decentralized technology, in waste reduction and performance improvement of Freight Transportation Management Systems (FTMS).Methodolog: The network analysis technique is used as one of the most valid multi-criteria decision-making models. We developed this model in four levels with four main criteria of performance wastes (including cost, time, trust and security and safety), and fourteen sub-criteria, considering the blockchain technologies in four areas of digital infrastructure, visibility, transparency, and smart contracts.Findings: Findings indicate that each of these technologies, individually and collectively, has reduced the waste of road freight management systems. The digital infrastructure technology reduced time and cost waste by 46.44% and 53.56%, respectively. Visibility has reduced 23.99%, 22.30%, and 53.71% of the wastes of cost, time, and safety, respectively. The transparency technology has influenced time and trust and security by 22.63% and 77.37%, respectively, and smart contracts affected the two above waste categories by 88.81% and 11.19%, respectively. The most effective wastes were identified as transportation costs, control costs, transparency in providing information, control of product conditions, and driver monitoring.Originality/Value: This study identified the most crucial road freight transport wastes and made it possible to determine priorities in various areas of blockchain technologies for future investment to improve the FTMS performance, and the findings of this study might be a starting point for future studies in this context.